Pendampingan Praktik Ubudiyah Bagi Jama’ah Masjid At-Taubah Kalangan Mojoseto Gondang Nganjuk - Hamdi, Mohamad Mustafid (LP3M STAI Darussalam Krempyang Nganjuk, 2019)
The worship practice orientation program is carried out by the KPM Team in the Kalangan Hamlet of Mojoseto Village by inviting the assisted partners along with the maghrib prayer congregation at the Taubah mosque in the Mojoseto Gondang Nganjuk hamlet in the lecture and question and answer method. The approach in this service uses the Asset-Based Community Development (ABCD) approach. The results of this assistance research are able to increase knowledge for worshipers, the realization of the prosperity of the mosque, the creation of a new spirit in carrying out daily worship and the creation of cooperation between parties in fostering the community.